Mobile-bed similitude evaluation of hydraulic sediment response models. Issue 1 (2nd January 2019) - Mustafa, Muhammed T.; Cox, Amanda L.; Davinroy, Robert D.; Krischel, Bradley J.; Nguyen, Ivan H.
Abstract : A form of small-scale physical modelling, known as Hydraulic Sediment Response modelling, was evaluated for mobile-bed similitude by analysing bathymetry, and dimensionless hydraulic and sediment-transport parameters. Two small-scale physical models were established for two different prototype reaches of the Mississippi River: the Upper Browns Bar reach and the Waters Point reach. To obtain prototype hydraulic conditions, one-dimensional numerical modelling was used to simulate steady flow in both reaches. Bathymetry was analysed by comparing cross-sectional flow areas, top widths, and hydraulic depths between the prototypes and the physical models. Acceptable agreement was found in the replication of the prototype bathymetry conditions for both reaches, taking into consideration the natural channel variability observed between different prototype surveys. Dimensionless sediment-transport parameters and spatial distributions of normalized Shields parameters were compared between the prototype numerical simulations and the physical models. Similar trends in the distribution of Shields parameters were observed.